Substrates and moisture content for seed germination test of Apuleia leiocarpa (Vog.) Macbr. - Padilha, Matheus Santin; Sobral, Lúcia Salengue; Abreu, Lucilene de; Baretta, Carolina Riviera Duarte Maluche (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
The substrate and amount of water used are determinant factors for conducting the germination test, affecting the growth of the embryo and the formation of the seedling. The objective of this work was to identify the ideal substrate and the moisture content for the seed germination test of Apuleia leiocarpa. The treatments consisted of substrates: paper towels (RP) and blotter paper (SP), moistened with water volumes equivalent to 2.0; 2.5 and 3.0 times the dry paper mass; sand (SA) and vermiculite (SV) moistened with an amount of water corresponding to 50, 60 and 70% of its field capacity. The germination tests were conducted in a constant temperature germinator of 25° C. The variables under evaluation were normal seedlings, abnormal seedlings, first germination count, germination speed index, average germination time and relative germination frequency. The experiment was conducted in a completely randomized design with three replicates of 50 seeds. Seed germination was not influenced by the water volumes used. Only the substrates showed differences, and the paper towel substrate is better for the germination test of Apuleia leiocarpa seeds, while the blotter paper is not recommended for the germination test of this species.